Polyethylene glycol-b-poly(lactic acid) polymersomes as vehicles for enzyme replacement therapy. (December 2017) - Kelly, Jessica M; Gross, Amanda L; Martin, Douglas R; Byrne, Mark E
Aim: Polymersomes are created to deliver an enzyme-based therapy to the brain in lysosomal storage disease patients.Materials & methods: Polymersomes are formed via the injection method using poly(ethylene glycol)-b-poly(lactic acid) (PEGPLA) and bound to apolipoprotein E, to create a brain-targeted delivery vehicle.Results: Polymersomes have a smallest average diameter of 145 ± 21 nm and encapsulate β-galactosidase at 72.0 ± 12.2% efficiency. PEGPLA polymersomes demonstrate limited release at physiologic pH (7.4), with a burst release at the acidic pH (4.8) of the lysosome. PEGPLA polymersomes facilitate delivery of active β-galactosidase to an in vitro model of GM1 gangliosidosis.Conclusion: The foundation has been laid for testing of PEGPLA polymersomes to deliver enzymatic treatments to the brain in lysosomal storage disorders for the first time.